PENGARUH DESAIN TAMPILAN WEBSITE, HARGA DAN PROMOSI PENJUALAN TERHADAP KEPUASAN PELANGGAN DAN MINAT BELI ULANG PADA MARKETPLACE SHOPEE DI KOTAPEKANBARU - Indirwan Indirwan; Restuti Sri; Nursanti Aida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
Onlineshops or marketplace in Indonesia has been widely carried out and has been proven to have a positive influence and big profits for online business actors. In Indonesia, there are several marketplaces that are active and always provide innovation in order to obtain customer satisfaction. Some of them are Tokopedia, Bukalapak, Lazada, Blibli, JD.ID, Zalora and Shopee. In this study, the object of research that will be selected is the Shopee marketplace. Based on data on the number of visitors, Shopee has a fairly stable line graph although it also decreased in 2019 in the 3rd quarter. Shopee is also a marketplace with the top one popularity in Indonesia from 2019 quarter 4 to 2020 quarter 2. Therefore, this study will discuss the influence of website display design, prices and sales promotions on customer satisfaction and repurchase interest in the Shopee marketplace. The total respondents in this research are 125 people with the sample collection method using the Non Probability Sampling technique by means of Purposive Sampling. The analytical method used in this research is Path Analysis. The results obtained are Website Display Design, Price and Sales Promotion variables have a positive and significant influence on Shopee Customer Satisfaction in Pekanbaru City. Then the Variables of Website Display Design, Price and Sales Promotion have a positive and significant influence on Shopee customers' repurchase interest in Pekanbaru City. Then the variables of Website Display Design, Price and Sales Promotion have a positive and significant influence on Repurchase Interest through Shopee Customer Satisfaction in Pekanbaru City. This shows that the Customer Satisfaction variable is able to mediate the relationship between Website Display Design and Repurchase Interest.Keywords : promotion, price, respondents, significant, path analysis